FUNGSI KPU DALAM PENETAPAN VERIFIKASI PARTAI POLITIK PESERTA PEMILU DI KPU KOTA SUNGAI PENUH - Faisal Amri (Gapenas Publisher, 2023)
The General Election Commission as an institution that is given a mandate based on realizing people's sovereignty, organizes general elections, to elect regional heads and people's representatives in the legislature. The purpose of this paper is to identify and analyze in depth the function of the general election commission in determining the verification of political parties participating in elections. For this reason, this research was conducted using a conceptual approach, statutory approach, historical approach and case approach. The results of the study show that the election result decisions issued by the KPU fall into the category of state administrative decisions because they fulfill the elements of a decision of a state administration official such as the KPU as an institution authorized to decide election results based on their duties and functions in holding general elections based on regulatory provisions. legislation and code of ethics of election organizers. The decision on the election results issued by the general election commission is concrete in nature and clearly stipulates. This decision creates legal consequences for a person or civil legal entity involved in the election administration. The process of validating and determining general election decisions is not solely based on the decision-making mechanism within the KPU institution itself but has been preceded by the process of holding elections in accordance with statutory regulations